2007
DOI: 10.1016/j.bbabio.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Differing responses of the two forms of photosystem II carbonic anhydrase to chloride, cations, and pH

Abstract: The effects of Cl(-), Mn(2+), Ca(2+), and pH on extrinsic and intrinsic photosystem II carbonic anhydrase activity were compared. Under the conditions of our in vitro experiments, extrinsic CA activity, located on the OEC33 protein, was optimum at about 30 mM Cl(-), and strongly inhibited above this concentration. This enzyme is activated by Mn(2+) and stimulated somewhat by Ca(2+). The OEC33 showed dehydration activity that is optimum at pH 6 or below. In contrast, intrinsic CA activity found in the PSII comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…and Mn 2? on tCA was also similar to that on Photosystem II activities (Stemler 1986(Stemler , 1997Lu and Stemler 2007).…”
Section: Thylakoid Ca Versus Photosynthetic Oxygen Evolutionsupporting
confidence: 68%
See 1 more Smart Citation
“…and Mn 2? on tCA was also similar to that on Photosystem II activities (Stemler 1986(Stemler , 1997Lu and Stemler 2007).…”
Section: Thylakoid Ca Versus Photosynthetic Oxygen Evolutionsupporting
confidence: 68%
“…(Tripathy and Mohanty 1980;Rashid et al 1991;Stemler 1997). The effects of Clon tCA was similar to that on Photosystem II activities (Stemler 1986(Stemler , 1997Lu and Stemler 2007). The effects of Ca 2?…”
Section: Thylakoid Ca Versus Photosynthetic Oxygen Evolutionsupporting
confidence: 56%
“…It could not be excluded that the activity of PSII was sup pressed because of the dysfunction of the water oxidizing complex. It was found that the features of dependence of the oxygen evolving function of PSII from maize and pea on Cl -or Ca 2+ concentrations was similar to the same dependence of its CA activity [106]. As to the nature of such connection, contradictory results have been obtained in different laboratories: dehydration CA activi ty was significantly increased after removing external pro teins of the water oxidizing complex [94,102]; the CA activity of PSII membranes was decreased by removing the proteins of this complex [116]; relatively high CA activity of PSII membranes was quite variable, but after removal of proteins of the water oxidizing complex, CA activity was not observed either in the solubilized proteins or in the core complex [117].…”
Section: Functions Of Carbonic Anhydrases In Higher Plantsmentioning
confidence: 69%
“…the replacement of the zinc with divalent iron in γ CA from M. thermophila led to increase in the CA activ ity under anaerobic conditions [39]). According to the authors of [106], the activity of PSII core complex results from the activity of CaMn4 complex together with its immediate surroundings. It is possible that the high molecular mass activity carrier is not the individual pro tein but a structure made by amino acids of neighboring proteins, which resembles the structure of CAs of γ fam ily in which the active site is formed by amino acids of dif ferent protein subunits.…”
Section: Functions Of Carbonic Anhydrases In Higher Plantsmentioning
confidence: 99%
“…As for another CA in PSII-membranes, which was called ‘extrinsic’ [70], or ‘low molecular mass’ [62,64], it has been suggested that PsbO, a manganese-stabilising protein of the oxygen-evolving complex, has CA activity [70,75]. This suggestion was oppugned [76], and it was later proven that the isolated protein PsbO did not demonstrate CA activity, and that the elimination of PsbO in PSII-membranes by treatment with salts did not lead to a decrease of their CA activity [77].…”
Section: Carbonic Anhydrases In Chloroplastsmentioning
confidence: 99%